Pathomorphological findings of gastrointestinal pythiosis in a dog (Indian Journal of Veterinary Pathology, 2025)
Intestinal pythiosis is a life threatening disease in dogs caused by fungus like organism called Pythium insidiosum. Gross examination revealed thickened intestinal wall with firm irregular masses on the serosal surface. Histopathological analysis revealed that the mass primarily consisted of fibrous tissue with multiple necrotic areas which were surrounded by macrophages, epithelioid cells, giant cells, lymphocytes and few plasma cells. In haematoxylin and eosin, both the longitudinal and transverse sections of tubuliform structures were observed within the necrotic areas. Periodic Acid-Schiff staining revealed pink fungal elements scattered in necrotic areas, while Grocott methenamine silver nitrate staining highlighted the fungal hyphae in the periphery of the necrotic regions with dark staining. Based on the histopathological and histochemical findings, it was concluded as gastrointestinal pythiosis in a dog.